2019
DOI: 10.1093/bioinformatics/btz812
|View full text |Cite
|
Sign up to set email alerts
|

YY1 is a cis-regulator in the organoid models of high mammographic density

Abstract: Motivation Our previous study has shown that ERBB2 is overexpressed in the organoid model of MCF10A when the stiffness of the microenvironment is increased to that of high mammographic density (MD). We now aim to identify key transcription factors (TFs) and functional enhancers that regulate processes associated with increased stiffness of the microenvironment in the organoid models of premalignant human mammary cell lines. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…After six days of treatment, the colonies were fixed, and no significant growth suppression was observed. Previously, we showed that the YY1 transcription factor plays a role in reversing aberrant polarity [ 19 ] and has a causal effect on the regulation of ERBB2 [ 16 ]. YY1 is involved in differentiation and proliferation, is overexpressed in cancer [ 32 ], and its genetic manipulation has been associated with phenotypic reversion between MCF10A and MCF7 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After six days of treatment, the colonies were fixed, and no significant growth suppression was observed. Previously, we showed that the YY1 transcription factor plays a role in reversing aberrant polarity [ 19 ] and has a causal effect on the regulation of ERBB2 [ 16 ]. YY1 is involved in differentiation and proliferation, is overexpressed in cancer [ 32 ], and its genetic manipulation has been associated with phenotypic reversion between MCF10A and MCF7 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our hypothesis is formulated based on two key observations: CD36 is downregulated in FBs of non-cancerous breast tissues with high mammographic density (MD) [ 10 ], where MD is associated with an increased breast cancer risk [ 11 , 12 , 13 ]; and normal FBs have been shown to have an anti-tumorigenic function through paracrine signaling [ 2 , 14 , 15 ]. Moreover, tissues with high MD, as well as tumor epithelial cells, secrete activin A, which is known to downregulate CD36 in FBs in ex vivo samples [ 10 ] as well as 3D models of MD [ 16 ]. Activin A is one of the secreted macromolecules that is overexpressed by cancer cells [ 17 , 18 ]; it is a member of the TGFβ superfamily of cytokines and, like TGFβ, signals through pSmad 2/3 effectors to activate cell cycle checkpoints in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…During different times, the ratio of radiation therapy has shown a relatively escalating trend, which may indicate doctors’ increasing tendency to use radiation therapy as an adjuvant method for surgery. Based on the IPTW calculated according to all the covariables that mislead treatment allocation, allocation bias was attenuated mainly ( 20 ). The significant treatment effect of adjuvant radiotherapy in the original cohort was also noted in the adjusted groups based on IPTW.…”
Section: Discussionmentioning
confidence: 99%
“…Inverse probability of treatment weighting (IPTW) was used to balance the bias of confounding factors that may affect radiotherapy allocation ( 20 ). We calculated the standardized mean difference (SMD) to assess the balance of baseline characteristics after IPTW.…”
Section: Methodsmentioning
confidence: 99%
“…To predict TFs regulating a query gene set, BART first apply Model-based Analysis of Regulation of Gene Expression (MARGE) (8) to derive a genomic cis-regulatory (enhancer) profile from the input gene set using a semi-supervised learning approach leveraging compendium ChIP-seq data for active enhancer histone mark H3K27ac, then generate a ranked list of TFs that have a highly correlated binding profile with the cis-regulatory profile. While proven to work for identifying functional TFs from many case studies (7,(9)(10)(11)(12), BART requires users to download large ChIP-seq data libraries that can be storage and memory-consuming, and sometimes runs slow primarily due to step-wise regression computation in MARGE.…”
Section: Introductionmentioning
confidence: 99%